Cardiomyocytes self-powered polymer microrobot - Kim, J.; Yang, S.; Baek, J.; Chun, K.; Kim, H.C.; Yoon, E.-S.; Park, S. (TRANSDUCERS and EUROSENSORS '07 - 4th International Conference on Solid-State Sensors, Actuators and Microsystems, 2007)
We established a novel method to fabricate a micro-machine that can actuate for long-term in physiological condition. Backbone of micro machine is built with bio-compatible material of PDMS by using specially designed 3D molding aligner. The high generative force of hybrid actuator is realized based on selective cell culture on groove surface that leads higher concentration of cells. Those key techniques enable the developed micro-machines to work for two weeks in medium condition. For performance demonstration of micro-machine, we construct a tripod micro-machine and observe sustained and synchronous locomotion in medium condition for almost two weeks-period. ？2007 IEEE.